Didactic Kerygma in the Synoptic Gospels - Vincent, John J. (Scottish journal of theology, 1957)
‘Kerygma’ is probably the most popular catch-word of contemporary Anglo-Saxon biblical theology. It purports to sum up what the NT has to say in a single word; it is taken over gratefully by systematicians and preachers as the longawaited ‘conclusion’ of the NT critics; it is a point from which other elements can be judged and pronounced more or less Christian.